2015
DOI: 10.1371/journal.pone.0128011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Autophagy-Inducing Ingredient of Areca Nut on Tumor Cells

Abstract: Areca nut (AN) is a popular carcinogen used by about 0.6-1.2 billion people worldwide. Although AN contains apoptosis-inducing ingredients, we previously demonstrated that both AN extract (ANE) and its 30-100 kDa fraction (ANE 30-100K) predominantly induce autophagic cell death in both normal and malignant cells. In this study, we further explored the action mechanism of ANE 30-100K-induced autophagy (AIA) in Jurkat T lymphocytes and carcinoma cell lines including OECM-1 (mouth), CE81T/VGH (esophagus), SCC25 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Although cytotoxic and autophagic effects of ANE and ANE 30‐100K were revealed, it is thought that oral tumor cells receiving sublethal concentrations of these AN ingredients might exhibit higher but cytoprotective autophagy activities against stressed conditions in AN chewers. This speculation is further verified in our recent studies that long‐term treatment of malignant cells with non‐cytotoxic concentrations of ANE or ANE 30‐100K (both ≤1.25 μg/mL) result in increased resistance against stressed conditions such as cisplatin and serum deprivation through elevated autophagic activities . Similar increased cisplatin resistance was also observed in oral carcinoma cell lines after 6‐day ANE (3 μg/mL) treatment …”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although cytotoxic and autophagic effects of ANE and ANE 30‐100K were revealed, it is thought that oral tumor cells receiving sublethal concentrations of these AN ingredients might exhibit higher but cytoprotective autophagy activities against stressed conditions in AN chewers. This speculation is further verified in our recent studies that long‐term treatment of malignant cells with non‐cytotoxic concentrations of ANE or ANE 30‐100K (both ≤1.25 μg/mL) result in increased resistance against stressed conditions such as cisplatin and serum deprivation through elevated autophagic activities . Similar increased cisplatin resistance was also observed in oral carcinoma cell lines after 6‐day ANE (3 μg/mL) treatment …”
Section: Introductionsupporting
confidence: 73%
“…We also found that the activity of autophagy‐inducing AN ingredient (AIAI) present in ANE 30‐100K is sensitive to both cellulase and proteinase K, suggesting this ingredient to be a proteoglycan or glycoprotein . Furthermore, ANE 30‐100K‐induced autophagic activity is dependent on reactive oxygen species, Beclin‐1, and Atg5 . Although cytotoxic and autophagic effects of ANE and ANE 30‐100K were revealed, it is thought that oral tumor cells receiving sublethal concentrations of these AN ingredients might exhibit higher but cytoprotective autophagy activities against stressed conditions in AN chewers.…”
Section: Introductionmentioning
confidence: 93%
“…These results probably reflect the conclusion that crude drug numbers 102 and 106 induced cell growth by inducing autophagic activity, but further investigations are needed to confirm the findings. In fact, crude drug number 107 (Binroji; areca) has been reported to induce autophagy in several cell lines, such as leukemic Jurkat T cells [39] and oral carcinoma cells (OECM-1), Cal-27, and Scc-9 [40] by activating the AMPK/mTOR signaling pathway after accumulating reactive oxygen species [40]. However, the relationship between autophagy and crude drug numbers 102 (Hishinomi; water chestnut) or 106 (Biwayo; loquat leaf) has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these treated cells exhibit stronger resistance against hypoxia, anti-cancer drugs, and serum starvation. Finally, upregulated autophagy is illustrated to be responsible for the increased tolerance of chronic ANE-and ANE 30-100K-treated cancer cells against drugs and serum deprivation [48,49]. Additionally, autophagy mediators Beclin 1 and ATG5 are shown to be required for ANE 30-100K-induced autophagy; whereas the role of AMP-activated protein kinase may be cancer-dependent [49].…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 98%
“…Finally, upregulated autophagy is illustrated to be responsible for the increased tolerance of chronic ANE-and ANE 30-100K-treated cancer cells against drugs and serum deprivation [48,49]. Additionally, autophagy mediators Beclin 1 and ATG5 are shown to be required for ANE 30-100K-induced autophagy; whereas the role of AMP-activated protein kinase may be cancer-dependent [49]. Collectively, our studies indicate that the autophagy-stimulating activity of AN may be tumor supportive, i.e., as those of RASdriven cancers, malignant cells developed in AN-addicted users might become autophagy-addicted.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 99%